If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4x + -5) = 0 Reorder the terms: 2(-5 + 4x) = 0 (-5 * 2 + 4x * 2) = 0 (-10 + 8x) = 0 Solving -10 + 8x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 8x = 0 + 10 Combine like terms: -10 + 10 = 0 0 + 8x = 0 + 10 8x = 0 + 10 Combine like terms: 0 + 10 = 10 8x = 10 Divide each side by '8'. x = 1.25 Simplifying x = 1.25
| 7x+6=2(3x+2) | | 4(5x-1)=3(4x+12) | | 2(3x+5)-3=16 | | 3(8x+2)-4x=36 | | 3x+4(2x-3)=10 | | 9x+2(x+7)=36 | | 7(5x-2)-8(4x+1)=5 | | 6(4X+3)-9(2X+1)=21 | | 3(3X+5)+2(3X-7)=19 | | 3(9X+4)=5(5X+4) | | 5(7X-1)=11(3X+2) | | 100-96=31y-35y | | 6(3X+2)=4(4X+7) | | -14m+8m=6-60 | | 9p+5q=63 | | 0=-9t | | 3(X+0.3)=1-X | | 3t+9t=20-10+26 | | 3x+14x-5=0 | | 7(a+3)=49 | | 3(a-1)=2(a+1) | | 13-13=2w-w | | -97-10x=9x+7 | | 7=7c-7 | | 3x+7=-45+10x | | x-9x=80 | | 4e-9=3 | | 3-0.8X=7-X | | x-w=y | | 2-0.66X=5-X | | -55+7=8n | | 4x+33=11x-30 |